Implementation of Public Private Partnership in The Development of Tourism in Sumenep District - Arimurti Kriswibowo; Eka Arum Pramestya; Khusnul Prasetyo (Program Pascasarjana Universitas Negeri Makassar, 2020)
The development of the tourism sector in Sumenep City continues to be encouraged to improve the community's economy and increase Regional Original Revenue. But unfortunately the target of foreign tourist visits can not be achieved because of the availability of inadequate infrastructure. To meet these shortcomings, the Sumenep City Government established a partnership with PT. Persada Investama Karya Utama to establish a three-star hotel